January 2021 and COVID-19 in Portugal: The Deadliest Month since 1919 - Filipe Froes; Marta Reis; António Diniz (Acta Médica Portuguesa)
The COVID-19 pandemic was the second pandemic of the 21st century and lasted 1150 days, from March 11, 2020, to May 5, 2023. It was one of the deadliest pandemics of the last century, alongside the ‘Spanish flu’ pandemic of 1918-1919. In Portugal, it was responsible for the deaths of 26 655 residents, with the year 2021 recording the highest mortality, with 11 991 deaths. In the first three years of the pandemic, all-cause mortality in Portugal exceeded 1200 deaths per 100 000 inhabitants, representing the highest values since 1957. The greatest impact of the pandemic occurred between December 2020 and February 2021, with 37 days of more than 4000 hospital admission beds occupied daily, 39 days of more than 600 intensive care unit beds occupied daily, and 20 days with more than 200 daily deaths. The month with the greatest impact was January 2021, with 5805 deaths due to COVID-19. The peak of hospital admissions occurred on January 31, 2021, with 6869 beds occupied, and the peak of mortality was on January 30, 2021, with 297 deaths. In absolute numbers, the monthly all-cause mortality in January 2021 in Portugal was the highest recorded since 1919.